EFEKTIVITAS MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN CERITA FIKSI: EFEKTIVITAS MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN CERITA FIKSI - Fitriani, Liswina; Nurjamaludin, Muhammad (Pendidikan Guru Sekolah Dasar Institut Pendidikan Indonesia Garut, 2020)
This research aims to see the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) model to improve the ability to read comprehension of fiction of student in fourth grade of SDIT Persis 99 Rancabango. The type of this research is a quantitative research with experimental methods (pre-experimental) in the form of one-group pretest-posttest design. The population this research were all fourth grade students, totaling 45 students. This research used purposive samplingtechnique. So the samples aree 25 students from IVA class. The instruments used in this research were tests and observation sheets. The results showed that the Cooperative Integrated Reading and Composition (CIRC) model was effective in increasing the ability to read comprehension of students’ fiction stories in class IV SDIT Persis 99 Rancabango. This conclusion is obtained through the acquisition of values before getting treatment which shows an average value of 45.68 and after receiving treatment of 75.24. This is corroborated by the results of the t-test that show = 14.9348> t table = 2.0639. Based on the analysis of the data that has been done, the research results obtained show that HO is rejected and Ha is accepted. Therefore,the Cooperative Integrated Reading and Composition (CIRC) model is effective in improving the ability to read fiction story comprehension in Class IV SDIT Persis 99 Rancabango. Because of the limitations of researchers in conducting research, the researcher suggests to the next researcher to retest the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) model with broader problems